Zebrafish in the sea of mineral (iron, zinc, and copper) metabolism - Zhao, Lu; Xia, Zhidan; Wang, Fudi (Frontiers in Pharmacology, 2014)
Iron, copper, zinc and eight other minerals are classified as essential trace elements because they present in minute in vivo quantities and are essential for life. Because either excess or insufficient levels of trace elements can be detrimental to life (causing human diseases such as iron-deficiency anemia, hemochromatosis, Menkes syndrome and Wilson’s disease), the endogenous levels of trace minerals must be tightly regulated. Many studies have demonstrated the existence of systems that maintain trace element homeostasis, and these systems are highly conserved in multiple species ranging from yeast to mice. As a model for studying trace mineral metabolism, the zebrafish is indispensable to researchers. Several large-scale mutagenesis screens have been performed in zebrafish, and these screens led to the identification of a series of metal transporters and the generation of several mutagenesis lines, providing an in-depth functional analysis at the system level. Moreover, because of their developmental advantages, zebrafish have also been used in mineral metabolism‒related chemical screens and toxicology studies. Here, we systematically review the major findings of trace element homeostasis studies using the zebrafish model. We also provide a homology analysis of trace mineral transporters in fish, mice and humans. Finally, we discuss the evidence that zebrafish are an ideal experimental tool for uncovering novel mechanisms of trace mineral metabolism and for improving approaches to treat mineral imbalance‒related diseases.